Analysis of Drainage Channels using Storm Water Management Model (SWMM) (Case Study : Bungo Mas Housing Phase 1 Bungo Pasang Village, Koto Tangah District, Padang City) - Erniati Rahmadiah; Jonni Mardizal (CIVED, 2025)
Drainage channels are water buildings that have an important function to channel excess water. With good drainage channels, excess water can be channeled and reduce the potential for waterlogging or flooding. Bungo Mas Tahap 1 Housing is located in Bungo Pasang Village which often experiences flooding or waterlogging due to high rainfall or long duration of rain. The problem of waterlogging in this area really needs attention because it disrupts various activities of the surrounding community and causes many losses. In addition to high rainfall, garbage and silt deposits in drainage channels are considered to be one of the causes of flooding. Therefore, it is necessary to analyze the existing drainage channels in Bungo Mas Tahap 1 Housing. The analysis process requires rainfall data for the last 10 years and the existing condition of the existing channels in the housing. One solution to assist in analyzing channels is using the Storm Water Management Model application (SWMM 5.2). After analysis of the channel, it was found that there was runoff in several channels so that the existing drainage was not effective because the dimensions of the channel were still not enough to accommodate the flow of water. Waterlogging that occurred in Bungo Mas Housing Phase 1 on the 2nd, 5th and 10th anniversary reached successive runoff peaks of 639.40 liters/s, 806.26 liters/s, and 914.87 liters/s which have been analyzed using SWMM 5.2 software.